Release of Serratia entomophila from prill formulations is affected by soil moisture - O'Callaghan, M.; Gerard, E.M.; Johnson, V.W.; Townsend, R.J.; Jackson, T.A. (New Zealand Plant Protection, 2002)
The bacterium Serratia entomophila has been incorporated into prill formulations to improve distribution and application of this insect pathogen to pasture for biological control of the New Zealand grass grub Costelytra zealandica While bacteria can survive in ambient conditions for long periods within the prills their field efficacy depends on successful release of bacteria from the prills and colonisation of the surrounding soil Laboratory experiments were conducted to determine the effects of soil moisture on rate of release of bacteria from prill formulations Prills were held in soil adjusted to four soil moisture contents (ranging from field capacity to wilting point) and the release of bacteria was determined by dilution plating Bacteria were released most rapidly at high soil moistures and populations were maintained at 103104 colony forming units per g soil in most treatments Measurement of release of S entomophila from prills in soil cores subjected to various watering regimes demonstrated that free soil water is important for distributing bacterial inoculum throughout soil profile